2002
DOI: 10.1002/nav.10042
|View full text |Cite
|
Sign up to set email alerts
|

Determination of burn‐in parameters and residual life for highly reliable products

Abstract: Today, many products are designed and manufactured to function for a long period of time before they fail. Determining product reliability is a great challenge to manufacturers of highly reliable products with only a relatively short period of time available for internal life testing. In particular, it may be difficult to determine optimal burn-in parameters and characterize the residual life distribution. A promising alternative is to use data on a quality characteristic (QC) whose degradation over time can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 15 publications
0
73
0
Order By: Relevance
“…Under a recognized definition of lifetime, that is, first hitting time (FHT) [6,7], many RUL estimation approaches have been reported in literature [8][9][10]. References [6,11] provide a detailed overview of the degradation modeling and RUL predicting method.…”
Section: Introductionmentioning
confidence: 99%
“…Under a recognized definition of lifetime, that is, first hitting time (FHT) [6,7], many RUL estimation approaches have been reported in literature [8][9][10]. References [6,11] provide a detailed overview of the degradation modeling and RUL predicting method.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [7] has studied the two kinds of the lifetime prediction based on Gamma processes. Pan [8] proposes a bivariate BirnbaumSaunders distribution and its marginal distributions to approximate the reliability function [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing, however, that Tseng et al [13] restricted their attention to the case (1) (2) ( ) ( ) t t Λ = Λ in their study, because they concluded that it was rather difficult to obtain an explicit form of the lifetime distribution when (1) (2) ( ) ( ) t t Λ ≠ Λ . Therefore, they only proposed a general Wiener process model form with two transformed time scales without any essential studies or applications.…”
Section: Introductionmentioning
confidence: 99%